2018
DOI: 10.1007/s12031-018-1159-2
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Signaling in Sodium Azide-Treated Oligodendrocytes Restores Mitochondrial Functions

Abstract: Mitochondrial dysfunctions mark a critical step in many central nervous system (CNS) pathologies, including multiple sclerosis (MS). Such dysfunctions lead to depolarization of mitochondrial membranes and imbalanced redox homeostasis. In this context, reactive oxygen species (ROS) are potentially deleterious but can also act as an important signaling step for cellular maintenance. The transcription factor nuclear factor (erythroid-derived 2)-like 2 (Nrf2), the key regulator in the cellular oxidative stress-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Complex IV inhibition by sublethal doses of sodium azide briefly prior to or throughout OPC differentiation substantially impaired the formation of complex oligodendrocyte processes [ 64 ]. The adverse effect of sodium azide on the mitochondria was intensified in Nrf2-knockdown cells and partly counteracted in Nrf2-hyperactivated (via Keap1 knockdown) cells, implying the importance of antioxidant defence [ 232 ]. In addition, homozygous deletion of succinate dehydrogenase subunit D, an important component of both the citric acid cycle and ETC complex II, hindered neuronal and oligodendrocyte (but not astrocyte) differentiation causing brain atrophy [ 233 ].…”
Section: The Interplay Between Ros/rcs (Epi)genetics Mitochondria Cell Signalling and Opc Differentiationmentioning
confidence: 99%
“…Complex IV inhibition by sublethal doses of sodium azide briefly prior to or throughout OPC differentiation substantially impaired the formation of complex oligodendrocyte processes [ 64 ]. The adverse effect of sodium azide on the mitochondria was intensified in Nrf2-knockdown cells and partly counteracted in Nrf2-hyperactivated (via Keap1 knockdown) cells, implying the importance of antioxidant defence [ 232 ]. In addition, homozygous deletion of succinate dehydrogenase subunit D, an important component of both the citric acid cycle and ETC complex II, hindered neuronal and oligodendrocyte (but not astrocyte) differentiation causing brain atrophy [ 233 ].…”
Section: The Interplay Between Ros/rcs (Epi)genetics Mitochondria Cell Signalling and Opc Differentiationmentioning
confidence: 99%
“…Sodium azide (NaN 3 ) is an inhibitor of cytochrome c oxidase related to the oxidative respiratory chain, and low temperature enables to lead to a decrease in enzyme activity, both of which can reduce the production of ATP. [31][32][33][34] Thus, we first examined the role of energy in the cellular uptake of EVs-based nanodrugs (EVs, HRE, ED, and HRED) in SKOV3/DOX cells by treating with 4 °C or mitochondrial inhibitor NaN 3 . As expected, the results indicated that when SKOV3/DOX cells were incubated at 4 °C or treated with mitochondrial inhibitor NaN 3 , the internalization capacity of PKH67-EVs, PKH67-HRE, ED, and HRED were dramatically reduced, suggesting that the intracellular uptakes of EVs-based nanodrugs (EVs, HRE, ED, and HRED) were energy dissipation process (Figure 5d).…”
Section: Resultsmentioning
confidence: 99%
“…Further, a successful, direct pharmacological activation of Nrf2 target genes by methysticin has already been shown in vitro and in vivo in another context [ 24 , 25 ]. Interestingly, Cao et al [ 26 ] reported that cyanidin-induced Nrf2 overexpression reduced the relative mRNA expression of Sox9 and Col II in the murine embryonic mesenchymal progenitor cell line C3H10T1/2.…”
Section: Discussionmentioning
confidence: 99%